Prijelazne elektromagnetske pojave pri sklapanju malih induktivnih i kapacitivnih struja u visokonaponskim postrojenjima : doktorski rad - Bojić, Srećko; Uglešić, Ivo (Zagreb, S. Bojić ; Fakultet elektrotehnike i računarstva, 2015)
SAŽETAK: Rad obraduje tematiku prijelaznih elektromagnetskih pojava svojstvenih za sklapanje prekidacem malih induktivnih i kapacitivnih struja u strujnom krugu izmjenicne struje visokonaponskog (VN) postrojenja. Cilj istraživanja usmjeren je na kvantificiranje amplitudnih i frekvencijskih karakteristika prijelaznih elektromagnetskih pojava nastalih sklapanjem prekidacem, polazeci od pretpostavke poznavanja uzroka, mjesta nastanka i nacina širenja istih u realnim pogonskim uvjetima VN postrojenja. Kvantifikacija karakteristicnih promatranih i ocekivanih pojava provedeno je na odabranim slucajevima sklapanja prekidacem: sklapanje VN kompenzacijske prigušnice u 110 kV postrojenju i neopterecenog dalekovoda 400 kV, raznih duljina i u razlicitim mrežnim konfiguracijama. Eksperimentalni dio istraživanja temeljen je na sveobuhvatnoj analizi, optimiranju i laboratorijskoj pripremi VN slabo prigušenih kapacitivnih djelila te provedbi opsežnih mjerenja prijelaznih pojava pri sklapanju prekidacem, a rezultati mjerenja obradeni su primjenom matematicko statistickih metoda zbog stohasticnog karaktera istih. Istraživanja u podrucju sklapanja malih induktivnih struja dopunjena su rezultatima proracuna na simulacijskom modelu prigušnice, VN postrojenja i prikljucne mreže EMTP-ATP programom, a prekidac je modeliran s modelom luka, s promjenjivim otporom luka. Simulirana su stanja kontroliranog i nekontroliranog sklapanja, prijelazne pojave uslijed rezanja struje, stanja ponovnog i višestrukog ponovnog paljenja elektricnog luka. Sklapanjem neopterecenog VN dalekovoda istraženo je ponašanje prekidaca, kvantifikacija parametara prijelaznog povratnog napona pri sklapanju male kapacitivne struje te utjecaj kapaciteta kondenzatora, prikljucenih paralelno komorama prekidaca, na amplitudu i strminu prijelaznog povratnog napana. Rezultati mjerenja i statisticke obrade pokazuju zadovoljavajucu sukladnost s rezultatima ranije provedenih simulacija za razmatrana stanja. Provedena istraživanja potkrijepljena su brojnim mjerenim i racunskim oscilogramima, a matematicko statisticke analize pokazuju dobru podudarnost s ocekivanim amplitudno-frekvencijskim karakteristikama promatranih prijelaznih pojava što je i potvrdeno kroz simulacije i analize na racunalnim simulacijskim modelima. - KLJUCNE RIJECI: prijelazne elektromagnetske pojave, mala struja, sklapanje prekidacem, prigušnica, neoptereceni dalekovod, sinkrono sklapanje, elektricni luk, prenapon, mjerenje, visokonaponsko postrojenje
EXTENDED ABSTRACT: The thesis is the result of research in the field of transient electromagnetic (EM) phenomena related to switching of inductive and capacitive loads in high voltage (HV) switchyards, particularly in case of switching of small inductive and capacitive currents. Electromagnetic transient phenomena during the switching of small currents have been predominantly processed and analyzed through results of experimental research, measurement and testing in real HV switchyards, with addition of computer simulations necessary for comparative analysis and final conclusions. Introductory chapter (Introduction) presents the basic terminology associated with switching small inductive and capacitive currents by circuit breaker, with emphasis on the source and characteristics of the transients related to problems during switching. The mechanism of current interruption, the emergence, development and expansion of transients is described, with the entry in the field of electromagnetic compatibility due to amplitude and frequency characteristics of the observed transient phenomena in HV switchyards. The aim of the research has been directed at evaluating the amplitude-frequency characteristics of transient electromagnetic phenomena during switching of small inductive and capacitive currents in HV switchyards, starting from the hypothesis of knowledge of their causes, place of origin and methods of spreading in real operating conditions. Set of theoretical and experimental research activities, encompassing computer simulations, tests carried out on both laboratory model and the "living" HV switchyard, have been implemented and focused on amending the results of previous research of transient EM phenomena in HV switchyards. In the second chapter (Theoretical analysis of switching small inductive and capacitive currents) the cause and origin of the observed current-voltage transients associated with connecting and disconnecting of typical small inductive and capacitive current loads by circuit breaker are analyzed. Amplitude and frequency properties are also analyzed and projection of possible dangers for devices, equipment and HV switchyard as a whole is given together with depiction of preventive and protective measures application. Encompassed and considered typical theoretical cases are supported by practical examples based on the previously acquired experience and carried out experimental research. The third chapter (The measurements in high voltage switchyard) is dedicated to the preparation, organization and implementation of HV measurements and testing for two selected typical cases of switching small currents by circuit breaker in real switchyard, namely: the switching of HW shunt reactor in 110 kV HV switchyard and switching of unloaded HV 400 kV transmission line in various configurations. Special attention has been paid to the selection and preparation of measuring equipment in accordance with the amplitude and frequency characteristics of the expected transient phenomena in the field of research. Specially adapted weak damped capacitive voltage dividers have been developed and prepared for measurements in HV switchyard on the basis of the computations carried out on the simulation model using the EMTP-RV program and the extensive testing and measurement of amplitude-frequency response characteristics carried out on appropriate laboratory model. Researched and constructed model has been adapted with additional RLC filter, compensation element and attenuator at the end of the measuring cable in order to achieve the required reduction of the measured signal, frequency compensation and minimization of unwanted electromagnetic interference during measurements in the real switchyard. The research results are presented in the fourth chapter (Research results). The experimental part of the research has been based on implementing the comprehensive measurement of transient phenomena during switching. The measurement results have been further analyzed using mathematical and statistical methods due to stochastic nature of the observed transients determined by measurement. Experimental studies of the switching of small inductive currents have been supplemented by the results of computations carried out by EMTP-ATP software on simulation model of three-phase, three-column shunt reactor, HV switchyard and connecting network, while the circuit breaker has been modeled as electrical arc model with variable arc resistance, using the "black box" model and Schwartz/Avdonin’s differential equation to simulate the thermal phase of arc interrupting. Simulations have been carried out for controlled and uncontrolled switching of shunt reactor, transients due to small current cut-off, electric arc reigniting and phenomenon caused by multiple reigniting. By varying the parameters in the arc model, a satisfactory correspondence with the researched phenomena in the experimental part of the research has been achieved. Circuit breaker behavior, identification and quantification of the characteristic parameters of transient recovery voltage on circuit breaker contacts during switching of small capacitive currents have been experimentally determined by switching unloaded HV transmission lines in various configurations of transmission lines and surrounding networks, set in order to achieve different values of capacitive loads. The influence of capacitors (their capacitance) connected in parallel to circuit breaker chambers on the amplitude and steepness of initial transient recovery voltage has been investigated by repetitive switching cycles of the same test configurations. Results of measurements and statistically determined characteristic indicators have also shown satisfactory compliance with the results of simulations carried out for same configurations during previous research performed for the preparation of measurement. The research results presented in the thesis are supported by a numerous oscillograms acquired by measurements and computations that show characteristic details of observed phenomena in amplitude-time and frequency domain. In conclusion, the fifth chapter (Conclusion) gives the summary of the research by stating the most important results of research and emphasizing that the mathematical and statistical analysis show good agreement with the expected amplitude-frequency characteristics of the observed transients, which has been confirmed by model simulations. Finally, as a thesis results, achieved original scientific contributions are cited: o Confirmation and improvement of simulation model for switching small inductive and capacitive currents based on theoretical and experimental research in HV laboratory and real HV switchyards. o Development of the procedure and methodology for measurement and research in the primary part of the HV switchyards, which includes the development of laboratory model, construction of primary HV measuring devices, adjustment of their amplitude and frequency characteristics and verification of laboratory and simulation model. o Determining the impact of varying values of electrical arc model parameters on the simulation of transient phenomena caused by switching of small inductive currents by circuit breaker. - KEYWORDS: transient electromagnetic phenomena, small current, circuit breaker switching, shunt reactor, unloaded transmission line, synchronous switching, electrical arc, overvoltage, measurement, high-voltage switchyard
Na spor. nasl. str. naslov na eng. jeziku: Electromagnetic transients caused by switching small inductive and capacitive currents in high voltage switchyards : doctoral thesis
Bibliografija: str. 163 - 174. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje i popis objavljenih radova autora]